Kasztelan krakowski Jerzy ks. Zbaraski wobec zagrożenia granic Rzeczypospolitej ze strony Siedmiogrodu (Władza i polityka w czasach nowożytnych. Dyplomacja i sprawy wewnętrzne, 2020)
Prince Jerzy Zbaraski (1574–1631) was one of the most outstanding Polish politicians of the first half of 17th century. Since 1620 he held the prestigious office of castellan of Kraków. He was a recognized leader of the opposition in the second half of the reign of Sigismund III. Living permanently in Kraków, he carefully observed the actions of Bethlen Gábor, ruling in Transylvania, whom he considered as a faithful vasal of the Turkish Sultan. Zbaraski’s attitude to the Bethlen was ambivalent. On the one hand, the prince considered the ruler of Transylvania as a dangerous neighbor of the Commonwealth and warned the Polish king against him. On the other hand, he saw him as a potential ally against his own monarch. However, Bethlen’s efforts to obtain the Polish crown made the castellan of Kraków, dreaming of the Polish throne himself, perceive this neighbor with increasing reluctance. The article attempts to trace the attitude of prince Jerzy Zbaraski to the ruler of Transylvania in the years 1619–1629. The starting point for these considerations is the battle of Humienne (Hommonai) fought on November 23, 1619 (Jerzy Zbaraski was a resolute opponent of sending Polish troops to Transylvania). The final chord is the unexpected death of Bethlen Gábor, who died on November 15, 1629.